Near‐Infrared Light Triggered Silk Fibroin Scaffold for Photothermal Therapy and Tissue Repair of Bone Tumors. (16th December 2020) - Miao, Hao; Shen, Runqing; Zhang, Wenhai; Lin, Zaifu; Wang, Hao; Yang, Likun; Liu, Xiang‐Yang; Lin, Naibo
Abstract: Silk fibroin (SF) has attracted great interest in bone tissue engineering due to its extraordinary characteristics in terms of mechanical properties, biocompatibility, and biodegradability. SF scaffolds are assembled by biocompatible polydopamine nanoparticles at mesoscopic scale, which endows the scaffolds with a near‐infrared (NIR) light response for the treatment of bone tumors. The functionalized SF scaffold not only enhances the significant structure and performance of native SF scaffold for bone treatment and reconstruction, such as primary and mesoscopic structure, multi‐level pores, and biodegradation, as well as biocompatibility but also have excellent photothermal effect leading a significant cytotoxicity to MG63 cancer cells after NIR laser irradiation. Moreover, the penetration of NIR light in tissue is improved using an optical fiber, which demonstrates the obtained scaffolds' great potential in the application of photothermal therapy. Abstract : Polydopamine nanoparticles functionalized silk fibroin (PDA@SF) scaffolds are endowed with high photothermal efficiency, outstanding biocompatibility, controllable mechanical properties, and degradation performance to realize both the killing of bone tumor cells and the repairing of bone defects, which are potential candidates for bone tumor therapy.